Deseo y satisfacción, el camino orteguiano hacia los Estados Unidos de Europa, 1910-1949 (Estudios de Historia de España, 2016)
The aim of this article in to analyze synthetically the three main ideas in the Spanish philosopher Jose Ortega y Gasset’s thinking about his concept of Europe as the driving force of regeneration of his own motherland.
Keywords: History of thinking; Europe; Philosophy and Political Science